2017
DOI: 10.1080/15384101.2017.1312225
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in DNA damage response, a new characteristic of cells infected with latent HIV-1

Abstract: Viruses can interact with host cell molecules responsible for the recognition and repair of DNA lesions, resulting in dysfunctional DNA damage response (DDR). Cells with inefficient DDR are more vulnerable to therapeutic approaches that target DDR, thereby raising DNA damage to a threshold that triggers apoptosis. Here, we demonstrate that 2 Jurkat-derived cell lines with incorporated silent HIV-1 provirus show increases in DDR signaling that responds to formation of double strand DNA breaks (DSBs). We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 84 publications
(115 reference statements)
2
50
0
Order By: Relevance
“…We first selected primary naïve CD4 + T cells from peripheral blood mononuclear cells (PBMC) and primed them towards differentiation into nonpolarized (NP) cells, which resemble the phenotype of the T CM cells (Fig. 3e) (Bosque and Planelles, 2009; Piekna-Przybylska et al , 2017). Infections with HIV-1 were performed when cells were still in an activated stage, and latency was established by progression of activated cells to a quiescent, memory-like stage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We first selected primary naïve CD4 + T cells from peripheral blood mononuclear cells (PBMC) and primed them towards differentiation into nonpolarized (NP) cells, which resemble the phenotype of the T CM cells (Fig. 3e) (Bosque and Planelles, 2009; Piekna-Przybylska et al , 2017). Infections with HIV-1 were performed when cells were still in an activated stage, and latency was established by progression of activated cells to a quiescent, memory-like stage.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that HIV-1 latency in T CM cells affects cellular DDR, and results in increased susceptibility to DNA damage (Piekna-Przybylska et al , 2017). Pericytes are permissive to HIV-1 infection, although the rate of virus replication appears to be even lower than in astrocytes, where HIV-1 replication is also restricted (Nakagawa et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations